The impact of statistics training and education on reasoning performance - Valerjev, Pavle; Dujmović, Marin (23rd Psychology Days in Zadar: Book of Selected Proceedings, 2024)
Recent studies have shown that analytical reasoning is related to a number of individual factors including IQ, lower conservativism, as well as other cognitive and personality factors. These studies have been broad, without aiming at specific influences on the development of analytical reasoning. The aim of this study was to determine whether education level and statistics training affect performance in reasoning tasks. Large samples from Croatia and the UK completed the Test of Statistical Reasoning (TSR), as well as a set of modified reasoning tasks. Results revealed that participants with some statistics training performed better in both the reasoning tasks and the TSR. The main finding was a country by education level interaction. Education level had a significant effect on both reasoning and TSR performance in the UK sample (higher level related to better performance), but a non-significant effect in the Croatian sample. An interesting finding was that Croatian participants performed significantly better than their UK counterparts at earlier stages of education, but then plateaued. UK participants reached the same level of performance at later stages. These differences may be explained by the breadth and depth of high school education in Croatia compared to the UK. Overall, statistics training and higher education levels relate to more analytical and statistical reasoning.